Healthcare organizations in entrepreneurial ecosystems : an integrative framework and future research agenda - Poček, Jasna (Technology in Society, 2026)
Abstrasct Entrepreneurial ecosystems as lenses promoting innovation and entrepreneurship have attracted substantial interest in research. However attention towards the role of sector-specific actors, such as healthcare-related organizations, within entrepreneurial ecosystems remains underexplored. This paper investigates how healthcare-related organizations are conceptualized within entrepreneurial ecosystem research through an integrative review of the literature addressing EEs and healthcare. The findings show that healthcare entrepreneurs are often portrayed as actors addressing both commercial and public health purposes. Hospitals are perceived as laboratories of collaboration and learning, combining care delivery with innovation-oriented activities, while life sciences are seen as critical to regional innovation and development by attracting scientific knowledge and enabling translation into entrepreneurial opportunities. Institutional and resource dynamics are also perceived as important for healthcare and entrepreneurship ecosystems, through facilitation of resource mobilization and regulatory adaptation. Based on this review, the paper develops a framework that positions healthcare organizations within entrepreneurial ecosystems according to their degree of hybridity and ecosystem roles. This research contributes to EE literature by examining entrepreneurial ecosystems research through a sector-sensitive and relational perspective. The paper offers a framework and research agenda calling for more exploration of institutional complexity, patient-centred innovation, the evolving role of hospitals, and hybrid governance models in entrepreneurial ecosystems.
Keywords: Entrepreneurial ecosystem; Healthcare; Institutions; Technology